2016
DOI: 10.14238/pi46.6.2006.260-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a structured educational intervention on metabolic control of type-1 diabetes mellitus patients

Abstract: Background Children with type-1 diabetes face not only short-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
2
0
1
Order By: Relevance
“…In our study, there were more female subjects (15/26) compared to male subjects (11/26) (female: male ratio was 1,4:1). This baseline characteristic was similar to the national epidemiological data in Indonesia, which stated that the prevalence of type 1 DM in men was less than in women (45:55) [1,12]. However, another study demonstrated that the prevalence of type 1 DM was similar between men and women [13].…”
Section: Baseline Characteristicssupporting
confidence: 86%
See 1 more Smart Citation
“…In our study, there were more female subjects (15/26) compared to male subjects (11/26) (female: male ratio was 1,4:1). This baseline characteristic was similar to the national epidemiological data in Indonesia, which stated that the prevalence of type 1 DM in men was less than in women (45:55) [1,12]. However, another study demonstrated that the prevalence of type 1 DM was similar between men and women [13].…”
Section: Baseline Characteristicssupporting
confidence: 86%
“…However, another study demonstrated that the prevalence of type 1 DM was similar between men and women [13]. These differences might be caused by the difference in population, race, and the number of research subjects [12]. Based on the nutritional state, our data showed that the proportion of children with good nutrition status was higher compared to children with low nutrition status.…”
Section: Baseline Characteristicsmentioning
confidence: 62%
“…16 Hal ini dimungkinkan oleh adanya perbedaan pada jumlah populasi, ras, dan jumlah subjek penelitian. 17 Pubertas merupakan masa transisi antara masa kanakkanak dengan dewasa yang dipengaruhi oleh banyak faktor. Pada saat itu terjadi perubahan fisik dan psikologis karenaaktivitas endokrin.Di Amerika Serikat, kebanyakan anak perempuan akan mengalami pubertas pada usia 8-13 tahun, sedangkan anak lakilaki akan mengalami hal yang sama pada usia 9-14 tahun.…”
Section: Pembahasanunclassified
“…However, based on ISPAD data in the same year mentioned that gender differences to the incidence of T1DM did not occur as a whole worldwide [1]. These differences are due to differences in population, race, and number of research subjects [19].…”
Section: Subject Characteristicsmentioning
confidence: 99%